Household consumption in Singapore. - Hui, Derek. (2008)
In this paper, estimated disposable income is used primarily as an independent variable in modelling a suitable consumption function in Singapore's context. The Almost Ideal Demand System (AIDS) and the Linear Expenditure System (LES) are also used to obtain the price elasticities, subsistence and supernumerary levels of private expenditure.